Transcranial direct current stimulation improves muscle isokinetic performance of young trained individuals - Magalhaes Sales, M.; De Sousa, C. V.; Vieira Browne, R. A.; Bodnariuc Fontes, E.; Dos Reis Vieira Olher, R.; Ernesto, C.; Simoes, H. G. (Medicina dello Sport, 2016)
BACKGROUND: Here we investigated the effects of transcranial direct current stimulation (tDCS) applied over the left temporal lobe on isokinetic muscle performance in adults. METHODS: Nineteen trained male (25.16±3.96 years; 75.11±8.06 kg; 176.90±7.75 cm; 24.04±2.44 kg·m-2) received either the anodic (T3 of 10-20 EEG system) or sham stimulation for 20 min followed by maximal isokinetic leg extension testing. Each participant performed two sets of five repetitions, one at angular velocity of 60°·s-1 and another at 180°·s-1. RESULTS: The performance on both tested velocities showed significant improvements in the total work (tDCS=1132.9±207.0 J vs. Sham=1015.43±159.2 J; t=-2.275; P=0.035; effect size=0.6361 at 60°·s-1 and tDCS=823.7±135.5 J vs. Sham=746.3±105.0 J; t=-2.303; P=0.033; effect size=0.6385 at 180°·s-1). Additionally, peak torque showed a tendency to increase in anodic condition despite not statistically different (60°·s-1; P=0.055 and 180°·s-1; P=0.062). CONCLUSIONS: tDCS applied over the left temporal lobe of the cortex can improve isokinetic leg extension performance in trained adults.